GOOGLE CLASSROOM APPLICATION IN TEACHING WRITING AT ELEVEN GRADE STUDENTS OF SMA ISLAM 1 SURAKARTA - Devita Khusnul Kholifah; Sri Handayani (English Education Department Slamet Riyadi University Surakarta, 2023)
This study aims to analyze a ‘google classroom application in teaching writing’ at eleven grade students of SMA Islam 1 Surakarta. This study was carried out in the academic year 2021/2022 at eleven grade students SMA Islam 1 Surakarta. The researcher used qualitative descriptive method. The researcher took 34 students of SMA Islam 1 Surakarta as the sample. The researcher researcher used questionnaires and interview with the teacher and students. To collect the data of questionnaire and interview, the researcher use questionnaire by Google Form. The data from questionnaire were analysed by using Likert scale. After collecting the data the researcher analyzed the data by using data triangulation to analyzed qualitative data. The result of this research showed that the implementation of Google Classroom in Teaching Writing was the student’s responsibility is good enough. The strengths and weakness of Google Classroom in Teaching Writing was the students who feel they can focus on learning lessons using Google Classroom, which according to them, the learning media is very interesting and plentiful. Key words: Google Classroom, Writing, Online Learning.